The median Effective Dose (ED50) and the 95% Effective Dose (ED95) of alfentanil in inhibiting responses to cervical dilation when combined with ciprofol during hysteroscopic procedure: a prospective, double-blind, dose-finding clinical study - Run Gao; Shu-Xi Li; Yan-Hong Zhou; Li Xing; Jin-Peng Fu; Jian-Jun Shen; Xin-Zhong Chen; Li-Li Xu (BMC Anesthesiology)
Abstract Background Alfentanil, a short-acting µ opioid receptor agonist, has recently been confirmed that when combined with propofol for daytime hysteroscopy, it provided more stable hemodynamics compared with sufentanil, and has a lower incidence of hypoxemia and postoperative nausea and vomiting. The object of the trial was to determine the median effective dose (ED50) and the 95% effective dose (ED95) of alfentanil in inhibiting responses to cervical dilation when combined with ciprofol and explore the effect of alfentanil on reducing ciprofol requirement during hysteroscopy. Methods One hundred and forty patients scheduled hysteroscopy under monitored anesthesia care were randomized to receive a bolus of 8 µg·kg−1, 10 µg·kg−1, 12 µg·kg−1, 14 µg·kg−1 intravenous alfentanil or 0.15 µg⋅kg−1 intravenous sufentanil followed by a bolus of 0.5 mg·kg−1 ciprofol. Whether there was loss of response to cervical dilation or not in each patient was recorded. We used the probit analysis to determine ED50 and ED95 of alfentanil in inhibiting responses to cervical dilation when combined with ciprofol. The requirement of ciprofol, the emergence time, the visual analogue scale score of pain at five time points, and the incidence of adverse events were recorded. Results The calculated ED50 and ED95 of alfentanil were 9.73 [95% CI 8.57 to 10.56] µg·kg−1 and 15.02 [95% CI 13.57 to 18.12] µg·kg−1, respectively. Ciprofol requirements were lower in patients given 10 µg·kg−1 (0.795 [ 0.707 to 0.889] mg·kg−1), 12 µg·kg−1 (0.799 [0.601 to 0.913] mg·kg−1), and 14 µg·kg−1 (0.789 [0.660 to 0.968] mg·kg−1) alfentanil than those given 8 µg·kg−1 alfentanil (1.082 [ 0.853 to 1.271] mg·kg−1) alfentanil and 0.15 µg⋅kg−1 sufentanil (1.046 [0.861 to 1.427] mg·kg−1) (P < 0.001). Emergence time was lower in patients given 10 µg·kg−1 (0.9 [0.8 to 1.2] min), 12 µg·kg−1 (0.8 [0.6 to 1.0] min) than those given 8 µg·kg−1 (1.9 [1.0 to 2.8] min) and 14 µg·kg−1 (1.5 [1.0 to 2.3] min) alfentanil, and 0.15 µg·kg−1 sufentanil (1.4 [1.0 to 2.0] min) (P < 0.001). The visual analogue scale score of pain at the time of 30 min and 1 h after surgery was lower in patients given 10 µg·kg−1, 12 µg·kg−1, and 14 µg·kg−1 alfentanil when compared with 8 µg·kg−1 alfentanil and 0.15 µg⋅kg−1 sufentanil (P < 0.001). The incidence of intraoperative hypotension was lower in patients given 8 µg·kg−1, 10 µg·kg−1, 12 µg·kg−1 alfentanil, and 14 µg·kg−1 alfentanil than those given 0.15 µg·kg−1 sufentanil (P = 0.044), while the incidence of intraoperative desaturation was higher in patients given 14 µg·kg−1 alfentanil than those given 8 µg·kg−1, 10 µg·kg−1, and 12 µg·kg−1 alfentanil, and 0.15 µg·kg−1 sufentanil (P < 0.001). Conclusions For women undergoing hysteroscopic surgery, a dose of 10–12 µg·kg−1 of alfentanil was associated with significant ciprofol-sparing effect, earlier anesthesia emergence, better postoperative analgesia, and less unexpected hemodynamic events compared with sufentanil, but 14 µg·kg−1 alfentanil had the risk of transient desaturation and delayed anesthesia recovery. Indications and the optimal dose of alfentanil in this patient population need further clarification. Trial registration The study was then registered on January 24, 2024 at the Chinese Clinical Trial Registry which participates in the World Health Organization International Clinical Trials Registry Platform (Identifier: ChiCTR2400080232) before enrolling the first participant and written informed consent was obtained by each patient.